Being doctors and something more - Abd Razak, Dzulkifli (2004)
What did Albert Schweitzer, Norman Bethune and Ernesto Guevara have in common? No idea? Okay, how about Ibn Sina and Ungku Omar Ahmad? They were all legendary figures in medicine, though not normally regarded as heroes or icons by the medical fraternity. Still, they are highly exemplary doctors — unlike those who rarely touch our lives nowadays, as health gradually be comes big business. Take, for example, Dr Albert Schweitzer. He was not only a doctor but also a humanitarian, philosopher, philanthropist and theologian; an accomplished musician with his masterly work on Bach. He studied at the University of Strasbourg and became a doctor in 1913.